Bioethics and Anointing of the Sick - Tham, L.C., Joseph (Studia Bioethica, 2015)
The relation between bioethics and the sacrament of the sick appears, at the first glance, somewhat disjointed. Contemporary bioethical literature would rarely admit any dealings with faith practices and beliefs into its discussion. Recuperating some of these visions and applying them to current issues of bioethics would prove to be a very interesting adventure, especially in today’s context of high technology and increasingly dehumanized medicine. In its relation to the sacrament of the sick, a first aspect that could be touched upon is the relationship between faith and healing. But I am more interested in dedicating a greater space to the current debate of euthanasia and the “good death” seen under the light of this sacrament. A third point would relate to the pastoral application of the Christian interpretation of a “good death.”